Optimizing the refinement of merohedrally twinned P61 HIV‐1 protease–inhibitor cocrystal structures. Issue 3 (5th March 2020) - Lockbaum, Gordon J.; Leidner, Florian; Royer, William E.; Kurt Yilmaz, Nese; Schiffer, Celia A.
Abstract : In the present study, it is shown that refinement and the resulting structures of hexagonal HIV‐1 protease cocrystal structures can be markedly improved by choosing a lower symmetry space group ( P 61 ) and applying a twin law ( h, − h − k, − l ) to correct for merohedral twinning. Abstract : Twinning is a crystal‐growth anomaly in which protein monomers exist in different orientations but are related in a specific way, causing diffraction reflections to overlap. Twinning imposes additional symmetry on the data, often leading to the assignment of a higher symmetry space group. Specifically, in merohedral twinning, reflections from each monomer overlap and require a twin law to model unique structural data from overlapping reflections. Neglecting twinning in the crystallographic analysis of quasi‐rotationally symmetric homo‐oligomeric protein structures can mask the degree of structural non‐identity between monomers. In particular, any deviations from perfect symmetry will be lost if higher than appropriate symmetry is applied during crystallographic analysis. Such cases warrant choosing between the highest symmetry space group possible or determining whether the monomers have distinguishable structural asymmetries and thus require a lower symmetry space group and a twin law. Using hexagonal cocrystals of HIV‐1 protease, a C 2 ‐symmetric homodimer whose symmetry is broken by bound ligand, it is shown that both assigning a lower symmetry space group and applying a twin law during refinement are critical to achieving a structural model that more accurately fits the electron density. By re‐analyzing three recently published HIV‐1 protease structures, improvements in nearly every crystallographic metric are demonstrated. Most importantly, a procedure is demonstrated where the inhibitor can be reliably modeled in a single orientation. This protocol may be applicable to many other homo‐oligomers in the PDB.